Effect of preoperative oral rehydration before cesarean section on ultrasound assessment of gastric volume and intraoperative hemodynamic changes: a randomized controlled trial - Eriko Ijiri; Chie Mori; Tomoki Sasakawa (BMC Anesthesiology, 2023)
Abstract Background Cesarean section often requires an urgent transfusion load due to decreased blood pressure after spinal anesthesia. This prospective randomized study aimed to investigate whether a preoperative oral rehydration solution (ORS) stabilized perioperative circulatory dynamics. Methods Sixty-three parturients scheduled for cesarean section under combined spinal epidural anesthesia (CSEA) were randomly allocated to one of three groups: Group O received 500 mL ORS before bedtime and 500 mL 2 h before CSEA; Group M received mineral water instead of ORS; and Group C had no fluid intake (controls). After entering the operating room, stomach size was measured using ultrasound. Blood samples were obtained, and CSEA was induced. Vasopressors were administered when systolic blood pressure was < 90 mmHg or decreased by > 20%. As a vasopressor, phenylephrine (0.1 mg) was administered at ≥ 60 beats/min heart rate or ephedrine (5 mg) at < 60 beats/min heart rate. The primary outcome was the total number of vasopressor boluses administered. Secondary outcomes were the cross-sectional area of the stomach antrum, maternal plasma glucose levels, serum sodium levels, total intravenous fluid, bleeding volume, urine volume, operative time, and cord blood gas values after delivery. Results The total number of vasopressor boluses was lower in Group O than in Group C (P < 0.05). Group O had lower total dose of phenylephrine than Group C (P < 0.05). There were no significant differences between Group M and other groups. No differences were detected regarding secondary outcomes. Conclusions In women scheduled for cesarean section, preoperative ORS stabilized perioperative circulatory dynamics. Neither ORS nor mineral water consumption increased the stomach content volume. Trial Registration This trial is registered in the University Hospital Medical Information Network Clinical Trials Registry (UMIN000019825: Date of registration 17/11/2015).